The narrativization strategies of historical knowledge in Hayden White’s theory of history - Mishalova Олена (Actual Problems of Mind, 2023)
Abstract. The paper is devoted to the theory of history of the American philosopher of history Hayden White, in particular, to the strategies of narrativization of historical knowledge in his conception of historical narrative. White believed that there can be no science in the modern sense without theory. His research approach was largely influenced by Maurice Mandelbaum’s critical philosophy of history, which laid the analytical foundations of White’s theory of historical knowledge, Robin Collingwood’s philosophy of history, which drew his attention to the conceptual and methodological similarities between historiography and literature, and Arthur Danto’s analytical narrative philosophy of history, according to with which a historical fact is considered as a discursive phenomenon and a historical narrative фі a form of organization of historical knowledge in the temporal wholes. It should be stressed that White recognized the powerful influence that the ideas of Michel Foucault and French structuralist philosophers, in particular Roland Barthes and Jacques Derrida, had on the formation of his position. It is noted that White considered his approach to be modernist, but, as Ewa Domanska rightly points out, his works show features characteristic of postmodernist discourse, which confirms that White is a multidimensional and interdisciplinary researcher who combined the theory of historiography and literary theory into a broader reflection on the topic of narrative understanding of reality. According to White’s theory of historical knowledge, a historical narrative is a verbal structure in the form of narrative prose discourse that claims to be a model or sign of past structures and processes in order to explain what they were by representing them. He distinguishes the following levels of conceptualization of a historical work: chronicle; story; mode of emplotment; mode of argument; mode of ideological implication. Thus, three obvious dimensions of historical work are postulated: epistemological, aesthetic, and moral, as well as a deep metahistorical dimension on which uncritically accepted paradigms (or styles) of historical thinking function. It is emphasized that within the framework of the White’s conception of historical narrative, a certain scheme of twelve categories of historical thinking is proposed, similar to the twelve Kantianʼs a priori categories of pure reason - a set of conceptual tools, a specific combination of which will determine what form and content a particular historical narrative will take as a result, creating the «effect of reality». In other words, a historical narrative is a kind of puzzle that consists of various forms of narrativization of historical knowledge: explanation by emplotment (Romance, Comedy, Tragedy, Satire), explanation by formal argument (Formism, Organicism, Mechanism, Contextualism), and explanation by ideological implication (Conservatism, Liberalism, Radicalism, Anarchism). Precisely because the historical narrative is a discursive model of the unfolding of historical processes, events and phenomena, it creates the «effect of reality» that is, a verbal representation of these historical processes, events and phenomena - historical reality as a whole, and does not reflect it as it really was.